Time between endobronchial ultrasound needle passes as a metric to monitor progress of trainees. Issue 3 (4th March 2022) - Hassan, Maged; McDill, Helen; Falconer, William; Taylor, Lindsey; Howell, Timothy; Corcoran, John P; Daneshvar, Cyrus
ABSTRACT: Background: Methods to assess and track progress of new endobronchial ultrasound (EBUS) operators and trainees is desirable to ensure training goals and procedural competence are achieved. Relying on the diagnostic yield or on question-based assessments alone is not sufficient. This study examined the longitudinal change in times taken between needle passes (needle pass time; NPT) during EBUS lymph node sampling as a metric to monitor progress. Research Design and methods: :The EBUS database of a tertiary hospital was accessed to extract data on the first 50 EBUS procedures for three trainees. The NPT was derived using PACS images that are stored to document every needle pass during an EBUS procedure and an average NPT was calculated. Results: Between the three trainees, 157 procedures were carried out within the study period with 302 nodal stations sampled. The mean NPT (n = 204 stations) was 2:49 ± 0:49 mins. The mean node short axis diameter was 15.5 ± 8.7 mm. There was a negative correlation between node size and time per pass (r − 0.146, p = 0.045). The average NPT showed a negative correlation with procedure order through the first 50 procedures. Less variation between procedures was noted for the three trainees from the 30 th procedure onward. On multivariate regression, NPT was significantly associated with procedure order regardless of station sampled or lymph node diameter. Conclusion: NPT is novel, easy, and robust metric that can potentially help ensure EBUS trainees are advancing in a given training program.